The Self-rescue of Nokia Roles of Internal Resources and Capabilities in the Corporate Innovation - Feng, Junqi (2019)
This dissertation attempts to explore the theoretical application of the concepts including resources, dynamic capabilities and innovation within the case study of Nokia, in this way to study the relationship between internal resources, capabilities and the innovation of the enterprise. The motivation for this research is to explore the influence of internal resources and dynamic capabilities on corporate innovation.